2017
DOI: 10.4103/0366-6999.204920
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Levodopa Treatment Accelerates the Circadian Rhythm Dysfunction in a 6-hydroxydopamine Rat Model of Parkinson's Disease

Abstract: Background:Parkinson's disease (PD) patients with long-term levodopa (L-DOPA) treatment are suffering from severe circadian dysfunction. However, it is hard to distinguish that the circadian disturbance in patients is due to the disease progression itself, or is affected by L-DOPA replacement therapy. This study was to investigate the role of L-DOPA on the circadian dysfunction in a rat model of PD.Methods:The rat model of PD was constructed by a bilateral striatal injection with 6-hydroxydopamine (6-OHDA), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
18
1
2
Order By: Relevance
“…6-OHDA treatments in rodents have been found to deregulate circadian behavioral and physiological outputs, as well as the expression of clock genes in different brain regions [38,39,40,41]. Furthermore, a recent study reported that levodopa administration further modified hormone secretion levels and the expression profiles of some clock genes in specific brain regions in 6-OHDA treated-rats, corroborating the notion that the pro-drug may contribute to circadian alterations seen in PD patients [42]. Contrasting data relating to the effects of MPTP treatment on mouse circadian phenotypes were obtained [33,34,35] (Table 1).…”
Section: Circadian Abnormalities In Pd Pathologymentioning
confidence: 71%
“…6-OHDA treatments in rodents have been found to deregulate circadian behavioral and physiological outputs, as well as the expression of clock genes in different brain regions [38,39,40,41]. Furthermore, a recent study reported that levodopa administration further modified hormone secretion levels and the expression profiles of some clock genes in specific brain regions in 6-OHDA treated-rats, corroborating the notion that the pro-drug may contribute to circadian alterations seen in PD patients [42]. Contrasting data relating to the effects of MPTP treatment on mouse circadian phenotypes were obtained [33,34,35] (Table 1).…”
Section: Circadian Abnormalities In Pd Pathologymentioning
confidence: 71%
“…In this lesion model we also saw higher intrasomal asynuclein, demonstrating a pathological expression pattern similar to PD [37,38] that may contribute to greater neuroinflammation [39], whereas non-pathological a-synuclein is localized to neuronal processes and is thought to assist in neurotransmitter release [40]. While current pharmacological therapies for PD help manage symptoms [41,42], these therapies cannot delay symptom progression [43,44]. Because of these issues, a large portion of PD research has been devoted to development of disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 73%
“…In patients with Alzheimer's disease, rhythmic methylation of BMAL1 has been found to be changed in the brains of patients with Alzheimer's disease, suggesting that alterations in the DNA methylation of clock genes may contribute to cognitive loss and behavior changes in individuals with Alzheimer's disease (9). Animal models of Parkinson's disease with 6-hydroxydopamine (6-OHDA) also show decreased BMAL1 and RORα that persisted with levodopa treatment, indication that long-term levodopa treatment may impair circadian rhythm function (10). …”
Section: Circadian Rhythm In Degenerative Disease and Cancermentioning
confidence: 99%